Women’s Social Enterprise Organizational Performance Analysis: A Road to Sustainability - Andi Fauziah Yahya; Fitriyani Fitriyani (BASKARA : Journal of Business and Entrepreneurship, 2023)
With a high sense of empathy and sociality, women tend to engage in social entrepreneurship or participate in social activities to pursue not only profit but also social impact. In addition, social entrepreneurship has been believed to be able to address social problems and be the best way to build economic resilience and independence in societies. Through extensive research, social enterprises have proven to be providers of solutions to social problems. Therefore, ensuring the success and sustainability of social enterprises is a major challenge for female entrepreneurs. The aim of this study is to identify the current conditions of social entrepreneurship and the challenges they face to ensure their sustainability from a comprehensive management perspective. The research applies a qualitative research approach with several case study designs. Data obtained through observations and semistructured interviews with four CEOs and ten employees was processed and analyzed using McKinsey’s 7S model approach to determine the company’s current organizational performance. Performance analysis using McKinsey 7S Models at KWN Fatimah Az-Zahrah, Celebes Mushroom Farms, Café Tulus, and Café Mella House of Donuts has provided an illustration of their current condition and found that the three elements are not aligned with each other, mainly the elements strategy, system, and skills, and the two elements have gaps in the system and skills. These unbalanced elements and gaps will hinder these companies from achieving efficient performance and sustainability.